PTiP : a bumpy road to solar success - Soumonni, Diran; Maunder, Peta Krost (London : Wits Business School, 2018)
Not for the first time since opening his company's demonstration facility in the Stellenbosch Technopark, Professor Vivian Alberts - chief executive and co-founder of Photovoltaic Technology Intellectual Property Innovations (PTiP) - stood back and admired what he saw. Twenty years had passed since this academic physicist began working on thin-film photovoltaic (PV) technology. He believed it had the potential to make a significant impact on South Africa's energy problems and to capture a share of the international market. Interested parties, including Eskom, had come to see the facility, but by September 2016, Alberts had yet to sign his first deal to license and build a turnkey solar module factory. He was unwavering in his belief that PTiP had something the country needed, but he was also aware that if it didn't take off fairly soon, the commercial window of opportunity would close. What was the solution?
Originally Published InSoumonni, D., & Maunder, P. K. (2018). PTiP: A bumpy road to solar success. WBS-2017-11. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Alberts, Vivian; Photovoltaic Technology Intellectual Property Innovations; Photovoltaic power generation; Thin films -- Electric properties; Solar cells; Technological innovations -- South Africa; Success in business -- South Africa